Ambient radioactivity on a reconnaissance study tour of Bratislava – Dubai – Kathmandu – Nepal Himalaya - MOJZEŠ, Andrej; BIELIK, Miroslav; MARKO, František; MADARÁS, Ján; FEKETE, Kamil; SIMAN, Pavol; PAPČO, Juraj; SIGDEL, Ashok; ACHARYA, Subash (Contributions to Geophysics and Geodesy, 2020)
Ambient radioactivity originates mainly from natural sources and materials (rocks and soils, building and other man-made materials, and cosmic radiation), and less frequently from artificial radionuclides. A geoscientific comparative study of the geological structure of the Alpine-Carpathian and Himalayan mountain range systems primarily focused on the area of structure geology, tectonics, stratigraphy and petrology in connection with the in-situ sampling of magnetic susceptibility and radioactivity at rock outcrops was also utilized to perform continual monitoring and acquisition of the equivalent gamma dose rate values in the air of the surrounding environment. A Geiger-Müller dosimeter was used for continual recording at a sampling frequency of 2 minutes. Simultaneously, a data-logger was used to record the ambient temperature, humidity and pressure values at a sampling frequency of 4 minutes. The measurements cover the entire tour, in particular, Bratislava, Slovakia (42.5 hours) – flight (5.75 hours) – Dubai, United Arab Emirates (11.3 hours) – flight (4 hours) – Kathmandu, Nepal (12.2 days) – flight (4.8 hours) – Dubai (9 hours) – flight (6.25 hours) – Bratislava (48 hours) from 27 March 2019 to 15 April 2019. The levels of ambient radioactivity belonging to different environments are compared and discussed in the contribution. The differences are based on both the chemical composition of the geological basement and adequate building materials and the cosmic contribution. The results of the measurements show higher values of ambient radioactivity for the Nepal environments and lower values for Dubai, in comparison with Bratislava, and by far the highest, but safe values for international flights attributed to the high portion of cosmic radiation. The contribution was generated within the ambit of the research project APVV-16-0146 WECAFARE (WEstern CArpathians FAults REsearch) “Multidisciplinary research of the geophysical and structural parameters and environmental impacts of the faults of the Western Carpathians”.